Qualidade das informações contábeis e práticas ESG: o papel do índice ISE B3 na transparência e governança corporativa - Barbosa, Isabela Almeida Dias; Lopes, Samantha das Graças (Universidade Federal de São Carlos, 2025)
This study investigates the relationship between corporate sustainability practices—measured by participation in the Corporate Sustainability Index (ISE B3)—and the quality of financial information disclosed by publicly traded Brazilian companies. Based on a sample of 166 companies and 836 observations from 2021 to 2023, the study applies the Modified Jones Model to estimate discretionary accruals as a proxy for accounting quality. The results indicate that overall participation in the ISE is not statistically significant in improving information quality. However, when analyzing individual index dimensions, climate change-related practices were positively associated with accounting quality, while corporate governance showed a negative and statistically significant effect. These findings suggest that the effectiveness of ESG practices on financial transparency depends on real organizational commitment to sustainability rather than mere formal compliance.
Quality of accounting information and ESG practices: the role of the ISE B3 index in transparency and corporate governance
Keywords: Qualidade da informação contábil; ESG; ISE B3; Transparência; Governança corporativa; Accounting information quality; ESG; ISE B3; Transparency; Corporate governance; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA; 16. Paz, Justiça e Instituições Eficazes